Understanding ASEAN Peace Preservation Role in the Korean Peninsula - Rangga Amalul Akhli (Jurnal Hubungan Internasional, 2018)
Since its inception in 1967, ASEAN has an important role to establish regional security and peace building in Southeast Asia. That effort certainly continues up until now. Realizing that the peace preservation needs to be extended to its northern neighbor, ASEAN initiated mechanisms that would enable it to play greater role in the Korean peninsula. However, the association effort to preserve peace in the region is inseparable from criticism which stated that this association was not effective in reconciling the two Koreas. Amidst the pessimism of ASEAN's role in the Korean Peninsula, this paper is presented to respond that argument. Furthermore, by using the constructivism paradigm, this paper argues that the ASEAN approach that believes in norms building to address security challenges in the Korean peninsula uncovers space for peace preservation in other ways amid such options and mechanisms that other powers offer which in fact last briefly and exacerbate hostility. To conclude, the approach has been useful for several reasons, such as maintaining the continuity of the multilateralism ties with North Korea and being an important actor that can be trusted by the two Koreas in the midst of a vortex of influences involving the big powers competition.